The in vitro anti-mycobacterial activities of the novel tetramethylpiperidyl-substituted phenazines, B4121 and B4128 - Anderson, Ronald (University of Pretoria, 2013)
Thesis (DPhil (Medical Immunology))--University of Pretoria, 2007.